Driven by the markets? ECB sovereign bond purchases and the securities market programme - Ansgar Belke (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
After the dramatic rescue package for the euro area, the governing council of the European Central Bank decided to purchase European government bonds - to ensure an orderly monetary policy transmission mechanism. Many observers argued that, by bond purchases, national fiscal policies could from now on dominate the common monetary policy. This note argues that they are quite right. The ECB has indeed become more dependent in political and financial terms. The ECB has decided to sterilise its bond purchases - compensating those purchases through sales of other bonds or money market instruments to keep the overall money supply unaffected. This is to counter accusations that the ECB is monetizing government debt. This note addresses how effective these sterilisation policies are. One problem inherent in the sterilization approach is that it reshuffles only the liability side of the ECB's balance sheet. It is not well-suited to either diminish the bloated ECB balance sheet or to remove the potentially toxic covered or sovereign bonds from it. In addition, the intake of potentially toxic assets as collateral and by outright purchases in the central bank balance sheet artificially keeps the asset prices up and does not prevent the (quite intransparent) risk transfer from one group of countries to another to occur. Finally, sterilization takes place in a setting of still ultra-lax monetary policies, i.e. of new liquidity-enhancing operations with unlimited allotment, and, hence, does not appear to be overly irrelevant. A credible strategy to deal with the financial crisis should deal primarily with the asset side of the ECB balance sheet. [...]
Keywords: G32; E42; E51; E58; E63; 330; Accountability; bail-out; bond purchases; central bank independence; insolvency risk; Securities Markets Programme; transparency; Schuldenübernahme; Öffentliche Anleihe; Staatsbankrott; Geldpolitik; Internationale wirtschaftspolitische Koordination; Zentralbankautonomie; EU-Staaten